2019
DOI: 10.1002/jor.24287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dose and release rate of CTGF and TGFβ3 on avascular meniscus healing

Abstract: Meniscus tears in the avascular region rarely functionally heal due to poor intrinsic healing capacity, frequently resulting in tear propagation, followed by meniscus deterioration. Recently, we have reported that time-controlled application of connective tissue growth factor (CTGF) and transforming tissue growth factor β3 (TGFβ3) significantly improved healing of avascular meniscus tears by inducing recruitment and step-wise fibrocartilaginous differentiation of mesenchymal stem/progenitor cells (MSCs). In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…Interestingly, Yin et al (2016) have combined CTGF and TGF-β1 in a step-wise manner, which led to augmented tenogenic differentiation of MSCs, as well as to tendon-like tissue formation in the repair process of rat patella tendon defect. CTGF alone or in combination with TGF-β has also been associated with fibrocartilage formation in meniscal injury models (Lee et al, 2014;Tarafder et al, 2019). Therefore, as well as to minimize costs, we designed our study with administration of only one growth factor from the TGFβ family.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Yin et al (2016) have combined CTGF and TGF-β1 in a step-wise manner, which led to augmented tenogenic differentiation of MSCs, as well as to tendon-like tissue formation in the repair process of rat patella tendon defect. CTGF alone or in combination with TGF-β has also been associated with fibrocartilage formation in meniscal injury models (Lee et al, 2014;Tarafder et al, 2019). Therefore, as well as to minimize costs, we designed our study with administration of only one growth factor from the TGFβ family.…”
Section: Discussionmentioning
confidence: 99%
“…The avascular meniscal defect was completely filled with type 1 and 2 collagen as well as newly formed capillaries (He et al, 2011). Another in vitro study reported enhanced alignment of collagen fibers, fibrocartilaginous matrix elaboration and mechanical properties after supplementation with high-dose CTGF (1,000 ng/ml) and a slowed release rate of TGFβ3 (0.29 ± 0.1 ng/day) in a bovine meniscal explant tear model (Tarafder et al, 2019)…”
Section: Connective Tissue Growth Factormentioning
confidence: 98%
“…For example, Zhang et al (2016) demonstrated that a 3D-printed PCL scaffold with a mean pore size of 215 μm significantly enhanced seeded cell colonization and further improved meniscal regeneration. Aside from changing the scaffold porosity, the incorporation of chemotactic chemokines could be a promising avenue ( Tarafder et al, 2019 ; Baek et al, 2020 ; Zhu et al, 2020 ).…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%